Exploration of Gen Z perceptions of organizational culture, person organization fit and loyalty - Brown, Anne Brockseker (My University, 2025)
Generation Z (Gen Z), born 1995-2012, is projected to become the largest cohort in the U.S. workforce by 2030, coinciding with Baby Boomer retirements. As companies increasingly hire Gen Z, understanding their distinct values, expectations, and workplace behaviors is critical for retention. Organizational culture and employees’ sense of fit are strongly linked to organizational loyalty. This study examines how full-time Gen Z professionals in U.S.-based companies perceive organizational culture and person-organization fit, and how these perceptions influence loyalty. Using a basic qualitative design grounded in social constructionism, the study gathered insights through two rounds of semi-structured interviews and workplace artifacts. The research applied both Schein’s (1981, 1983) and Schein and Schein’s (2017) three levels of organizational culture framework and Kristof’s (1996) person-organization (PO) fit theory as a conceptual lens to explore how Gen Z interprets artifacts, values alignment, and underlying workplace assumptions. Findings show Gen Z needs to feel comfortable asking questions and strongly prefers flat organizational structures. They want cultures that promote learning and transparency from senior leaders. Participants emphasized the critical importance of aligning personal and professional values with company values. Career progression opportunities and supportive, positive, authentic environments foster loyalty, which for Gen Z is rooted in relationships and differs from traditional tenure-based definitions. The study offers organizational leaders and human resources development (HRD) executives’ practical strategies to improve Gen Z engagement and retention.
Keywords: Organizational culture; Generation Z; Person organization fit; Loyalty; Gen Z in the workplace; Schein's Three Levels of Organizational Culture